Application of targeted next-generation sequencing for pathogens diagnosis and drug resistance prediction in bronchoalveolar lavage fluid of pulmonary infections - Qiugui Xu; Qiumei Chen; Wen Qiu; Lili Liu; Wan Zeng; Jinling Chen; Yangyang Li; Zhen Guo; Ling Rong; Bigui Chen; Jinxiu Yao; Liye Yang (Frontiers in Cellular and Infection Microbiology)
BackgroundRecently, targeted next-generation sequencing (tNGS) have been extensively utilized for the identification of pathogens in pulmonary infections, there have been some studies systematically evaluating differences in the efficacy of tNGS and conventional microbiological tests (CMTs) in bronchoalveolar lavage fluid (BALF) specimens.MethodsA retrospective analysis was conducted on 203 patients with pulmonary infections treated in one tertiary hospital from July 2023 to February 2024. BALF specimens underwent parallel testing via tNGS and CMTs. Pathogen detection consistency, the drug resistance genes concordance with phenotypic drug sensitivity, and clinical impact of tNGS-guided therapy adjustments were analyzed. Furthermore, two patients with complex infections were selected for tNGS microbiological surveillance to evaluate the efficacy of monitoring severe pneumonia.ResultsThis study included 205 confirmed infectious BALF specimens (two patients were tested twice). tNGS identified 56 putative pathogens, compared to 20 by CMTs, with a significantly higher positive rate (99.5% vs. 35.6%, P<0.0001). The detection of pathogenic microorganisms using tNGS showed a high concordance rate with the results of CMTs. tNGS-guided therapy adjustments occurred in 17.2% (35/203) of patients. Resistance gene predictions aligned with the drug sensitivity results in 40% (6/15) of carbapenem-resistant organisms (CROs) and 80% (4/5) of methicillin-resistant Staphylococcus aureus (MRSA) cases. Additionally, for monitored two patients with severe pneumonia, the tNGS results were consistent with the culture and imaging test results during treatment.ConclusionsThe application of tNGS highlights its promise and significance in identifying potential pathogens, predicting drug resistance, and providing guidance for anti-infection therapies for severe pneumonia. It can be at least a complementary approach to CMTs reporting.